2003
DOI: 10.1177/1073191103010002001
|View full text |Cite
|
Sign up to set email alerts
|

WAIS-III Factor Index Score Patterns After Traumatic Brain Injury

Abstract: Profile subtypes, based on the Wechsler Adult Intelligence Scale-Third Edition (WAIS-III) factor index scores, were examined in a sample of 166 patients with traumatic brain injury (TBI) by means of a two-stage clustering procedure. Three reliable subtypes were found that were differentiated primarily by level of performance across all factor index scores, although each of them demonstrated a relative weakness on the Processing Speed index. These subtypes were then validated on the basis of demographic variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 22 publications
4
12
0
Order By: Relevance
“…The Spatial Span test from the Wechsler Memory Scale-3rd Edition (WMS-III; Wechsler, 1997b), which loaded on a working memory factor when not allowed to split between factors, loaded more strongly on the perceptual factor than it did on a working memory factor when split loadings were permitted. In studies of special clinical populations examining only WAIS-III subtests, factor analysis confirmed that nonverbal subtests, Picture Completion, Block Design, and Matrix Reasoning all loaded on the same factor (Jones et al, 2006;Ryan & Paolo, 2001;van der Heijden & Donders, 2003). These studies all support the hypothesis that the nonverbal subtests measure a single perceptual construct.…”
Section: Unravelling Nonverbal Cognitive Performance In Acquired Aphasiasupporting
confidence: 62%
See 1 more Smart Citation
“…The Spatial Span test from the Wechsler Memory Scale-3rd Edition (WMS-III; Wechsler, 1997b), which loaded on a working memory factor when not allowed to split between factors, loaded more strongly on the perceptual factor than it did on a working memory factor when split loadings were permitted. In studies of special clinical populations examining only WAIS-III subtests, factor analysis confirmed that nonverbal subtests, Picture Completion, Block Design, and Matrix Reasoning all loaded on the same factor (Jones et al, 2006;Ryan & Paolo, 2001;van der Heijden & Donders, 2003). These studies all support the hypothesis that the nonverbal subtests measure a single perceptual construct.…”
Section: Unravelling Nonverbal Cognitive Performance In Acquired Aphasiasupporting
confidence: 62%
“…Directly treating non-linguistic cognitive abilities in people with aphasia may improve everyday communication (Ramsberger, 2005). The underlying factor structure of nonverbal tasks has been well studied in healthy individuals (e.g., Leonberger, Nicks, Larrabee, & Goldfader, 1992;Tulsky & Price, 2003), but to a lesser extent in special clinical populations (Jones, van Schaik, & Witts, 2006;Ryan & Paolo, 2001;van der Heijden & Donders, 2003). Tulsky and Price (2003) showed that the nonverbal Performance IQ measures from the Wechsler Adult Intelligence Scale-3rd Edition (WAIS-III; Wechsler, 1997a), including Matrix Reasoning, Block Design, Picture Completion, and to a lesser extent Picture Arrangement, load strongly on a perceptual/nonverbal factor.…”
Section: Unravelling Nonverbal Cognitive Performance In Acquired Aphasiamentioning
confidence: 99%
“…Post-TBI neurocognitive deficits often occur across cognitive domains, including general intelligence (Catroppa et al, 2008), working memory (Schwartz et al, 2003), attention (DeJong & Donders, 2008; Mottram & Donders, 2005; Jacobs & Donders, 2008), executive functions (Yeates et al, 2002; Ganesalingam, Sanson, Anderson, & Yeates, 2006; Ganesalingam, Sanson, Anderson, & Yeates, 2007), and processing speed (Donders & Janke, 2008; Donders, 1997; Tremont, Mittenberg, & Miller, 1999; van der Heijden & Donders, 2003). Although deficits are greater in moderate to severe TBI (Schwartz et al, 2003; Catroppa et al, 2008; Yeates et al, 2002), existing research suggests that, relative to uncomplicated mild TBI and typically developing controls, children with complicated mild TBI often evidence impaired episodic memory and cognitive processing along with a diminished ability to manage cognitive interference (Levin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings have been observed previously with other psychometric tests after TBI. For example, Van der Heijden and Donders (2003) completed a cluster analysis on WAIS-III factor index scores following TBI. Similar to the current results, no clusters were found to be "unique" to TBI, but they did find that WAIS-III performance was related to injury severity-that is, the greater the injury severity, the poorer the overall level of performance.…”
Section: Discussionmentioning
confidence: 99%